RESPON PERTUMBUHAN BUD SET TANAMAN TEBU (Saccharum officinarum L) VARIETAS NXI 4T TERHADAP LAMA PERENDAMAN NATRIUM PARA-NITROFEL - Dwi Putri Saskia Maharani; Taufika, Ramadhan; Fisdiana, Usken; Hartatie, Dian (Fakultas Pertanian Universitas Janabadra, 2025)
National sugar production from 2021 to 2024 has fluctuated. Fluctuations in national sugar production are caused by sugar self-sufficiency not yet being achieved. One of the causes is that sugarcane plants experience a lot of nutrient deficiencies. These nutrients affect plant growth, one of which is the process of root formation. Efforts that can be made to initiate root formation are the use of ZPT Atonik which contains the active ingredient sodium para-nitrophel (CP6H4NO3Na) which is classified as an auxin hormone. This study used NXI 4T variety sugarcane seeds which are suitable for planting on dry or dry land, as well as rain-resistant land. The purpose of this study was to determine the effect of the duration of soaking in Sodium Para-Nitrophel on the growth of bud sets of NXI 4T sugarcane plants. This study used five treatments in sequence, namely sugarcane seeds were not soaked in sodium para-nitrophel solution, sugarcane seeds were soaked for 2 hours, 3 hours, 4 hours, 5 hours. The results of the study showed that the duration of sodium para-nitrophel immersion affected the growth of bud sets in the observation parameters of plant height, number of leaves, number of shoots and root wet weight, but did not affect the observation parameters of root dry weight.